Log in to add a comment

## Answers

X=sinФ-cosФ

y=sinФ+cosФ

dx/dФ = cosФ+sinФ

dy/dФ = cosФ-sinФ

dy/dx = (cosФ-sinФ)/(cosФ+sinФ)

y=sinФ+cosФ

dx/dФ = cosФ+sinФ

dy/dФ = cosФ-sinФ

dy/dx = (cosФ-sinФ)/(cosФ+sinФ)

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

x=sinФ-cosФ

Differentiating w.r.t 'Ф'

dx/dФ = cosФ + sinФ

y=sinФ+cosФ

Differentiating w.r.t. 'Ф'

dy/dФ = cosФ - sinФ

Now,

dy/dx = dy/dФ × dФ/dx

dy/dx = (cosФ-sinФ) × 1/(cosФ+sinФ)

dy/dx = (cosФ-sinФ)/(cosФ+sinФ)

Now you can rationalize,

dy/dx = (cosФ-sinФ)²/1

dy/dx = (cosФ-sinФ)²

Differentiating w.r.t 'Ф'

dx/dФ = cosФ + sinФ

y=sinФ+cosФ

Differentiating w.r.t. 'Ф'

dy/dФ = cosФ - sinФ

Now,

dy/dx = dy/dФ × dФ/dx

dy/dx = (cosФ-sinФ) × 1/(cosФ+sinФ)

dy/dx = (cosФ-sinФ)/(cosФ+sinФ)

Now you can rationalize,

dy/dx = (cosФ-sinФ)²/1

dy/dx = (cosФ-sinФ)²